La technique de l’arc segmenté. Contrôle de l’ancrage et modification significative du profil facial : une étude de cas - Ianni Filho, Daniel [UNESP]; Massahiro Takematsu, Nelson [UNESP]; Miyagi, Niomar [UNESP]; Borella, Luciana (Elsevier, 2008)
This article evaluates space closure mechanics efficiency in an extraction case where maximum anchorage was a requirement. The Segmented Arch Technique (SAT) was utilized as an anchorage control strategy to obtain maximum anterior retraction and, in consequence, significant facial profile change. A 20-year-10-month old woman needed severe labial and profile changes. The patient had four premolars extracted and SAT with type A mechanics [1] (Marcotte [2] activation protocol) was applied. The results showed significant reduction in labial protrusion and incisal angulation with effective anchorage control. The results were compared to others available in the literature derived from different techniques, where anterior retraction was also accomplished with maximum anchorage [3-7]. In conclusion, the SAT with type A mechanics has been shown to be another treatment option when significant changes in the soft-tissue profile are needed in extraction cases. © 2008. CEO. Published by Elsevier Masson SAS. All rights reserved.
Segmented arch technique. Anchorage control and significant facial profile change: A case report
Keywords: Anchorage; Segmented arch technique